ANALISIS KEMAMPUAN SISWA KELAS IV SEKOLAH DASAR SE-GUGUS II KECAMATAN TAMPAN KOTA PEKANBARU DALAM MENEMUKAN GAGASAN POKOK PADA TEKS BACAAN - Tri Andriyana Putri; Otang Kurniaman; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was effected by the problem of finding the idea of staple on reading text of elementary school students. This is apparent when the initial observation takes place in the SDN 188 Pekanabaru implemented during the activities of PPL taking place. This situation also occurs in other elementary schools. It can be seen from the results of their understanding in reading text they are reading. There are still students who experience difficulties in finding key ideas contained in the text of the readings. This study aims to describe the student ability of class IV SD in Cluster II subdistrict of Tampan Pekanbaru in finding the idea of reading text on the subject matter. This research uses a quantitative descriptive method with the subject consists of 108 students. Research instrument used in the form of a narrative shaved reading text consist of 10 paragraphs with the theme of “globalization”. The text of the readings taken from the education Citizenship bookclass IV with the Publisher Esis and Erlangga. Based on the results of the research, from 108 students there are 32 students got the category of very good (29.63%), 21 students who got the category good (19.44%), 31 student who got enough category (28.7%) and 24 students who got less categories (22.22%). Overall, the ability of the average of students was 72.69 by category is enough. This suggests that the ability of grade IV SD in Cluster II of Tampan subdistrict of Pekanbaru in finding the idea of reading text on the subject matter as a whole is sufficient.Key Words : ability, find the main idea